Bisexual Orientation, Divorce and Islamic Law in Indonesia: Legal Standing and Arguments - Warda Silwana Hikmah; Hasnan Bachtiar; Kukuh Dwi Kurniawan (Universitas Islam Negeri Jakarta, 2022)
Can the bisexual orientation in a marriage bond be considered a legal argument for formulating a verdict in the Indonesia Islamic courts? Does it have such a specific legal standing mentioned directly within any regulation covering the issue of Islamic private law? In answering both these questions, this article implements a normative-juridical inquiry that examines various rational possibilities in developing arguments of law. This article finds that in handling the case of bisexual orientation, the Indonesian legal system has remained a legal vacuum. Consequently, it seems it might not be a direct legal argument because it has no legal standing. This article argues that there is no single legal instrument has been imposed that explicitly mentions the case of the orientation. However, the judge may implement the analogous of the possibility of